Myelodysplastic syndrome hematopoietic stem cell. Issue 3 (29th October 2012) - Li, June
<x xml:space="preserve">Abstract</x> Myelodysplastic syndromes (MDSs) are clonal hematopoietic stem cell (HSC) malignancies that are characterized by ineffective hematopoiesis and frequent progression to acute myeloid leukemia (AML). Thus far, few treatments can actually alter the natural history of this disease. Allogeneic stem‐cell transplantation for high‐risk MDS is becoming the only curative therapy probably because of the improvement of bone marrow transplant procedures. The lack of other options underscores the urgent need to develop new therapy. The prevailing model suggests that genetic and/or epigenetic alterations that occur in HSCs or HSC niche compromise HSC function, resulting in MDS; therefore, MDS HSCs are likely the ideal targets for MDS treatment. Recent encouraging advances—capturing a molecular portrait of the whole genome of MDS CD34+ cells, including identifying altered signaling pathways and altered microRNAs—have improved our understanding of MDS pathogenesis and provided novel potential clinical targets for MDS. Here, I will briefly review the characteristics of MDS HSCs and discuss the therapeutic promise of targeting MDS HSCs.